2018
DOI: 10.1111/joor.12742
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orthodontic separator and short‐term fixed orthodontic appliance on inflammatory mediators and somatosensory function

Abstract: Summary Background Although inflammation can alter cytokines release and nerve function, it is not yet fully established if orthodontic‐induced inflammation can cause significant extraoral trigeminal somatosensory alterations and release of inflammatory chemical mediators. Objective The primary aim of this study was to investigate the impact of orthodontic separator and short‐term fixed orthodontic appliance on the extraoral trigeminal somatosensory function and concentrations of cytokines in the gingival crev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Thus, it is assumed that the individuals presently analysed had a ‘normal’ pain perception system, which confirms the unique participation of appliances on the perceived pain. Only small and temporary somatosensory manifestations, associated with insignificant changes in inflammatory cytokines, were also found in a study that evaluated pain after placement of orthodontic separators 34 . The aforementioned factors, associated with an evaluation period of 6 months, strengthen the present data, since this is the first study to consider such aspects when judging pain related to orthodontic therapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, it is assumed that the individuals presently analysed had a ‘normal’ pain perception system, which confirms the unique participation of appliances on the perceived pain. Only small and temporary somatosensory manifestations, associated with insignificant changes in inflammatory cytokines, were also found in a study that evaluated pain after placement of orthodontic separators 34 . The aforementioned factors, associated with an evaluation period of 6 months, strengthen the present data, since this is the first study to consider such aspects when judging pain related to orthodontic therapy.…”
Section: Discussionsupporting
confidence: 81%
“…Only small and temporary somatosensory manifestations, associated with insignificant changes in inflammatory cytokines, were also found in a study that evaluated pain after placement of orthodontic separators. 34 The aforementioned factors, associated with an evaluation period of 6 months, strengthen the present data, since this is the TA B L E 4 Comparison between groups concerning the frequency, number of individuals (n) and percentage (%) of utilization of analgesics after placement of appliances at T1 during the 7 days of period…”
Section: Ta B L Esupporting
confidence: 80%
“…Table 2 shows results for the somatosensory thresholds. Threshold values in TDP were consistent with those of prior research ( Sampaio et al, 2019 ; Arnstad et al, 2020 ; Truffyn et al, 2021 ). Autistic children and adolescents had lower pressure pain thresholds than their TDP ( t (1,69) = 2.51, p = 0.015).…”
Section: Resultssupporting
confidence: 88%
“…Similar findings have been observed in a study authored by Soltis and co-workers [18], pointing out that the proprioceptive discrimination of the force intensity applied on incisor was altered by the insertion of orthodontic forces. Recently, Sampaio and co-workers [32] assessed the effects of orthodontic separators on the extraoral somatosensory functions by means of a standardized battery of quantitative sensory testing. The authors found no changes at extra-oral trigeminal innervation, supporting that somatosensory alterations following periodontal pain are local phenomena and that regions remote from the teeth are not significantly affected.…”
Section: Discussionmentioning
confidence: 99%